Effect of Replacing Rice Bran with Aloe vera and Sunflower in Fermented Feed on Carcass, Internal Organs, and Abdominal Fat of Broiler Chickens - Zulfan Zulfan; Herawati Latif; Muhammad Aman Yaman; Vira Anatasha (Agricultural Faculty, 2022)
ABSTRACT. The purpose of this study was to examine replacement rice bran (RB) with the mixture of Aloe vera flour (AVF) + sunflower seed flour (SFS) within the fermented feed of which with the addition of other feed ingredients used to replace 25% of the commercial diet on carcass yields, internal organs, and abdominal fat of broilers. The study was conducted at the Field Laboratory of Animal Husbandry, the Faculty of Agriculture, Syiah Kuala University. The study used 100 chicks strain Cobb applied in a Completely Randomized Design with sub-samplings consisting of 5 treatments, 4 replicates, and 2 sub-samples. The treatments were 100% CP511 (control+) and 4 FF-based diets: FF3% RB (control-), FF3% AVF, FF3% SFS, and FF3% AVF + 3% SFS. The results of this study showed that replacing rice bran with AVS and SFS either exclusively or in combination in equal amount 3% each did not significantly affect (P0.05) the percentages of the carcass, cut-ups, internal organs, and abdominal fat of broilers. In conclusion, either Aloe vera or sunflower seed flour could be incorporated 3% each in a single source or in combination to replace rice bran within the fermented feed. without adverse effects on carcass yields and internal organs as well as abdominal fats of broilers.(Pengaruh penggantian dedak dengan tepung lidah buaya dan biji bunga matahari dalam bahan pakan fermentasi terhadap berat karkas, organ dalam dan lemak abdomen ayam broiler)ABSTRAK. Penelitian ini bertujuan untuk mengamati pengaruh penggantian dedak padi (DP) dengan campuran tepung lidah buaya (TLB) dan biji bunga matahari (TBM) dalam bahan pakan fermentasi yang tersusun dan beberapa bahan pakan lain yang digunakan untuk menggantikan 25% ransum komersil terhadap berat dan persentase karkas, organ dalam, dan lemak abdomen ayam broiler. Penelitian dilakukan di Laboratorium Lapangan Peternakan (LLP), Fakultas Pertanian, Universitas Syiah Kuala. Penelitian menggunakan 100 ekor anak ayam broiler strain Cobb. Rancangan yang digunakan adalah Rancangan Acak Lengkap sub sampel terdiri dari 5 perlakuan, 4 ulangan, dan 2 sub sampel. Hasil penelitian memperlihatkan bahwa penggunaan TLB yang dicampur dengan TBM masing-masing sebanyak 3% tidak berpengaruh nyata (P0,05) terhadap berat dan persentase karkas, organ dalam, dan lemak abdomen ayam broiler. Kesimpulannya, TLB dan TBM masing-masing 3% ataupun campurannya 6% dapat digunakan untuk menggantikan dedak padi dalam bahan pakan fermentasi.